The Tax Elasticity of Financial Statement Income: Implications for Current Reform Proposals - Dhammika Dharmapala (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Current reform proposals in international and corporate tax (most notably the OECD's GloBE proposal) envisage taxing financial statement income. This paper develops a conceptual framework – based on the literature on the elasticity of taxable income – for the welfare analysis of such proposals, and discusses the available evidence on the tax elasticity of financial statement income. The central conclusion is that the most relevant evidence suggests a large responsiveness of financial statement income to taxes (and hence, albeit with significant limitations and caveats, arguably a large deadweight loss). The paper also highlights the need for more evidence on this question.
Keywords: H25; M41; 330; international taxation; multinational firms; financial statement income; book-tax conformity